Following the edge of the flood: use of shallow-water habitat by larval silver carp Hypophthalmichthys molitrix in the upper Mississippi river system. Issue 1 (21st December 2020) - Chick, John H.; Colaninno, Carol E.; Beyer, Autumn M.; Brown, Kelly B.; Dopson, Curtis T.; Enzerink, Ariana O.; Goesmann, Stephanie R.; Higgins, Tom; Knutzen, Nigel Q.; Laute, Erin N.; Long, Paula M.; Ottenfeld, Paige L.; et al.
Abstract: We examined the use of "edge of flood" habitats by larval silver carp during the extensive flooding that occurred in Pool 26 of the Upper Mississippi River near Alton, IL, USA and St. Louis, MO, USA during the summer of 2015. We captured over 12, 700 individual fishes including eight taxa, over 12, 000 of which (> 95%) were larval silver carp between 5 and 21 mm standard length. Peak catch rates occurred near the confluence of the Illinois and Mississippi rivers. These findings suggest that larval silver carp have an affinity for edge of the flood habitat and further study is needed to better understand how this affects the dynamics of this invasive species in the Mississippi River. The high catch rates observed at the confluence of the Illinois and Mississippi rivers suggests that the Illinois River is an important source of larval silver carp to the Upper Mississippi River.